2008
DOI: 10.1016/j.plipres.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and function of polyacetylenes and allied natural products

Abstract: Polyacetylenic natural products are a substantial class of often unstable compounds containing a unique carbon-carbon triple bond functionality, that are intriguing for their wide variety of biochemical and ecological functions, economic potential, and surprising mode of biosynthesis. Isotopic tracer experiments between 1960 and 1990 demonstrated that the majority of these compounds are derived from fatty acid and polyketide precursors. During the past decade, research into the metabolism of polyacetylenes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
233
1
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(255 citation statements)
references
References 503 publications
(551 reference statements)
6
233
1
15
Order By: Relevance
“…Polyynes, namely polyacetylenes, have been found in many food and dietary plants [1][2][3][4][5]. To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyynes, namely polyacetylenes, have been found in many food and dietary plants [1][2][3][4][5]. To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacetylenic fatty acids, containing more than one triple bond in the molecule, are produced and sequestered by a wide variety of organisms in many environments; more than 2,000 of these molecules have been identified in higher plants, liverworts, mosses, fungi, marine sponges and algae 19 . Many polyacetylenics have highly potent biological activities, which are used in defence against pathogens and predators 3,12,15 , and some have been investigated as human anti-cancer and anti-microbial treatments 13,16,18,20 .…”
Section: Figure 5 | Phylogenetic Analysis Of Insect Desaturasesmentioning
confidence: 99%
“…The challenging chemistry and variety of potent biological activities of polyacetylenic fatty acids, which includes activities against cancer cells, infecting microbes and plant alleopathy [12][13][14][15][16][17][18][19][20] , have excited interest among natural-product prospectors and bioactive discovery programmes, and have propelled our interest in new molecular structures and biosynthetic origins. In this report, we describe a three-gene pathway isolated from the Australian soldier beetle C. lugubris, leading to an 18-carbon precursor of DHMA, and the first eukaryote biosynthesis of conjugated polyacetylenic compounds.…”
mentioning
confidence: 99%
“…The catalytic activity can be changed with the substituents on the N atom of the salts such as imidazolium, imidazolidinium or bisbenzimidazolium [5,8]. Carbon-carbon cross-coupling reactions, which play an important role in the synthesis of natural products, drug design and industrially important starting materials, have been an area of interest for organic chemists for a long time [9][10][11].…”
Section: Introductionmentioning
confidence: 99%